Muscarinic Acetylcholine Receptor Modulation of Mu (μ) Opioid Receptors in Adult Rat Sphenopalatine Ganglion Neurons - Margas, Wojciech (American Physiological Society, 2010)
The sphenopalatine ganglion (SPG) neurons represent the parasympathetic branch of the autonomic nervous system involved in controlling cerebral blood flow. In the present study, we examined the coupling mechanism between mu (μ) opioid receptors (MOR) and muscarinic acetylcholine receptors (mAChR) with Ca(2+) channels in acutely dissociated adult rat SPG neurons. Successful MOR activation was recorded in ∼40–45% of SPG neurons employing the whole cell variant of the patch-clamp technique. In addition, immunofluorescence assays indicated that MOR are not expressed in all SPG neurons while M(2) mAChR staining was evident in all neurons. The concentration-response relationships generated with morphine and [d-Ala2-N-Me-Phe4-Glycol5]-enkephalin (DAMGO) showed IC(50) values of 15.2 and 56.1 nM and maximal Ca(2+) current inhibition of 26.0 and 38.7%, respectively. Activation of MOR or M(2) mAChR with morphine or oxotremorine-methiodide (Oxo-M), respectively, resulted in voltage-dependent inhibition of Ca(2+) currents via coupling with Gα(i/o) protein subunits. The acute prolonged exposure (10 min) of neurons to morphine or Oxo-M led to the homologous desensitization of MOR and M(2) mAChR, respectively. The prolonged stimulation of M(2) mAChR with Oxo-M resulted in heterologous desensitization of morphine-mediated Ca(2+) current inhibition, and was sensitive to the M(2) mAChR blocker methoctramine. On the other hand, when the neurons were exposed to morphine or DAMGO for 10 min, heterologous desensitization of M(2) mAChR was not observed. These results suggest that in rat SPG neurons activation of M(2) mAChR likely modulates opioid transmission in the brain vasculature to adequately maintain cerebral blood flow.